The Effect of Propofol vs. Isoflurane Anesthesia on Postoperative Changes in Cerebrospinal Fluid Cytokine Levels: Results from a Randomized Trial - Berger, Miles; Ponnusamy, Vikram; Greene, Nathaniel; Cooter, Mary; Nadler, Jacob W.; Friedman, Allan; McDonagh, David L.; Laskowitz, Daniel T.; Newman, Mark F.; Shaw, Leslie M.; Warner, David S.; Mathew, Joseph P.; et al. (Frontiers in Immunology, 2017)
Introduction Aside from direct effects on neurotransmission, inhaled and intravenous anesthetics have immunomodulatory properties. In vitro and mouse model studies suggest that propofol inhibits, while isoflurane increases, neuroinflammation. If these findings translate to humans, they could be clinically important since neuroinflammation has detrimental effects on neurocognitive function in numerous disease states. Materials and methods To examine whether propofol and isoflurane differentially modulate neuroinflammation in humans, cytokines were measured in a secondary analysis of cerebrospinal fluid (CSF) samples from patients prospectively randomized to receive anesthetic maintenance with propofol vs. isoflurane (registered with http://www.clinicaltrials.gov, identifier NCT01640275). We measured CSF levels of EGF, eotaxin, G-CSF, GM-CSF, IFN-α2, IL-1RA, IL-6, IL-7, IL-8, IL-10, IP-10, MCP-1, MIP-1α, MIP-1β, and TNF-α before and 24 h after intracranial surgery in these study patients. Results After Bonferroni correction for multiple comparisons, we found significant increases from before to 24 h after surgery in G-CSF, IL-10, IL-1RA, IL-6, IL-8, IP-10, MCP-1, MIP-1α, MIP-1β, and TNF-α. However, we found no difference in cytokine levels at baseline or 24 h after surgery between propofol- (n = 19) and isoflurane-treated (n = 21) patients (p > 0.05 for all comparisons). Increases in CSF IL-6, IL-8, IP-10, and MCP-1 levels directly correlated with each other and with postoperative CSF elevations in tau, a neural injury biomarker. We observed CSF cytokine increases up to 10-fold higher after intracranial surgery than previously reported after other types of surgery. Discussion These data clarify the magnitude of neuroinflammation after intracranial surgery, and raise the possibility that a coordinated neuroinflammatory response may play a role in neural injury after surgery.